Kontrak Swap Komoditi: Satu Analisis Dari Perspektif Syariah - Nadhirah, Nordin; Wan Saifuldin, W.H.; Rahimah, Embong (2014)
Swap contract is an agreement between two parties which aimed at exchanging periodic cash flows. Commodity swap contract is one of the derivative instruments which the value depends on the value of the underlying assets, namely commodities. Swap contract emerged as a result of the advancement of financial engineering that is based on conventional economics. Therefore, further studies should be conducted to identify the extent of conventional commodity swap contracts meet the principles outlined in Islamic economics. This study analyzed the syariah issues in commodity swap crude palm oil and proposed potential syariah principles in the contract. In order to achieve this objective, the methods of interview and document analysis are used by reviewing the authoritative classical books of Fiqh. The result has shown that there are syariah issues such as gharar, usury and speculation in the contract. Thus, this study suggested the application of wa'd principle and bay„ al-murabahah/musawamah in syariah compliant commodity swap contracts.